A VIDA NA GRAÇA E AS IMPLICAÇÕES TEOLÓGICO-PASTORAIS NA VIDA PRESBITERAL (Razão e Fé, 2022)
The present article will aim to discuss the theological-pastoral implications of the Theology of Grace in the life of the priest in the light of the itinerary on divine Grace, its relationship with nature and freedom, in order to understand its action in priestly life. In order to reach our objective, which will be done through bibliographical research, we will go through the debate about Grace from the Tradition of the Church, with emphasis on the reflections of Gregory the Great in his Pastoral Rule and John Chrysostom in his work On the Priesthood, and also in the Magisterium of the Church, with the contributions of the Second Vatican Council (1962-65), the Exhortation Pastor Dabo Vobis (1992) and later, the Document of the Conference of Aparecida (2007), which bring relevant systematizations for the theme of the ordained ministry. Finally, we will address the current issues surrounding the theme in order to offer a greater understanding of the action of grace in the life of the Church through its ordained ministers.